Recent scaffold‐based tissue engineering approaches in premature ovarian failure treatment. (5th May 2022) - Zivari‐Ghader, Tayyebeh; Dolati, Sanam; Mehdizadeh, Amir; Davaran, Soodabeh; Rashidi, Mohammad Reza; Yousefi, Mehdi
Abstract: Recently, tissue engineering and regenerative medicine have received significant attention with outstanding advances. The main scope of this technology is to recover the damaged tissues and organs or to maintain and improve their function. One of the essential fields in tissue engineering is scaffold designing and construction, playing an integral role in damaged tissues reconstruction and repair. However, premature ovarian failure (POF) is a disorder causing many medical and psychological problems in women. POF treatment using tissue engineering and various scaffold has recently made tremendous and promising progress. Due to the importance of the subject, we have summarized the recently examined scaffolds in the treatment of POF in this review.